Increasing Women's Awareness and Concern for Breast Cancer through Health Education: Impact of Educational Programs on Early Detection and Prevention - Rita Rena Pudyastuti; Sujono Sujono; Kariyadi Kariyadi; Johanna Tomasoa (PT. Anagata Sembagi Education, 2025)
Breast cancer is one of the leading causes of death in women worldwide, with incidence rates increasing every year. Early detection and prevention are important steps in reducing mortality from this disease. Women's low awareness and understanding of breast cancer is a major barrier to early detection. This literature study aims to analyze the impact of health education programs on increasing women's awareness and concern about breast cancer, especially in the aspects of early detection and prevention. Based on the literature review, it was found that health education programs have a significant role in improving women's understanding of risk factors, early symptoms, and the importance of breast self-examination and clinical examination. A number of studies have shown that before receiving education, many women did not understand the importance of early detection and tended to neglect breast examination. After participating in the education program, there was an increase in knowledge and a positive change in attitude towards early detection, with more women willing to perform regular breast examinations. This study also revealed that interactive and community-based education methods are more effective than passive delivery of information. Thus, the results of this literature study confirm that health education is an effective strategy in increasing women's awareness and concern about breast cancer. The implementation of more innovative and technology-based education programs can be a solution in reaching more women, especially in areas with limited access to health services.